Educational Values of Religious Tolerance and Nationalism in Lamongan Islamic Boarding School - Nicky Estu Putu Muchtar; Imam Suprayogo; Triyo Supriyatno (State Islamic Institute of Madura, 2021)
This study regards the implementation of the educational values of religious tolerance and nationalism in IBS of Islam Al-Islam, IBS of Karangasem Muhammadiyah, IBS of Sunan Drajat, and IBS of Modern Muhammadiyah Lamongan. This study applied a qualitative approach, interpreted with phenomenology approach, and natural setting method. The techniques of data collection were through observation, interview and documentation. The results of the technique of data collection were through data obtained analysis, data condensation, data grouping and verification. Furthermore, the validity of the findings used a focus group discussion (FGD) to test the validity of the research data. The results of the study included the implementation of educational values of religious tolerance through the role of Kyai, habituation and Islamic boarding school’s learning. While the implementation of nationalism values was through formal learning, extra-curricular, organization, speech, mutual cooperation, ceremonies and PHBN (Memorial of The National Day).